Initial Validation of Hanson Sex Attitude Questionnaire (HSAQ) in Portuguese perpetrators of child sexual abuse and perpetrators of non-sexual crimes - Sousa, Marta (2024)
Cognitive distortions (CDs) are a crucial element in the etiology of child sexual offending, with most of the intervention programs targeting them to reduce the risk of sexual recidivism in perpetrators of child sexual abuse (CSA). Researchers have developed the Hanson Sex Attitude Questionnaire (HSAQ) to assess CDs. With a total sample of 256 participants, the Portuguese version of the HSAQ revealed a two- factor structure. The HSAQ subscales demonstrated good to acceptable psychometric properties in terms of internal consistency, as well as discriminant validity. One of the subscales also demonstrated conver-gent validity. Additionally, the two subscales exhibited differences between perpetrators of CSA with and without previous interventions, indicating known-groups validity. Overall, our findings partially support the use of the HSAQ in the forensic Portuguese population, underscor-ing its significance for clinical and research purposes. Nevertheless, particular caution is advised, especially regarding factor two